2022
DOI: 10.1021/acsami.2c03123
|View full text |Cite
|
Sign up to set email alerts
|

Mechanically Robust Irradiation, Atomic Oxygen, and Static-Durable CrOx/CuNi Coatings on Kapton Serving as Space Station Solar Cell Arrays

Abstract: The polymers that served for solar cell arrays are constantly subject to various hazards, such as atomic oxygen (AO), ion irradiation, or electrostatic discharge (ESD) events. To address these issues, we fabricated and sifted CrO0.16/CuNi-coated Kapton with a gradient structure with the goal of reaching an equilibrium between AO durability and resistance. The resulting material exhibits an impressively low E y of 6.61 × 10–26 cm3 atom–1, 2.20% of which was detected as pristine Kapton. Self-evolution of the CrO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Kapton ® films have been used in cardiovascular applications [ 22 ], space station solar cell arrays [ 23 ], and flexible electronic sensors [ 24 , 25 , 26 ]. Kapton ® films have also been used as stencil masks by our group and other researchers [ 15 , 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Kapton ® films have been used in cardiovascular applications [ 22 ], space station solar cell arrays [ 23 ], and flexible electronic sensors [ 24 , 25 , 26 ]. Kapton ® films have also been used as stencil masks by our group and other researchers [ 15 , 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…1b) and further relaxed. The Gibbs free energies of the reactions on the surfaces were calculated based on the following equations [39]: The charge difference calculations were performed for the Cr 2 O3/ CuS interface system via the subtraction of separately calculated charges for the Cr 2 O 3 and CuS layers. The analysis of the conducted calculations was done through Transition State Tools for VASP by Henkelman group [45].…”
Section: Theoretical Simulationsmentioning
confidence: 99%
“…It is, therefore, reasonable to design heterostructure between Cr 2 O 3 and CuS which combines the advantageous features of both individual components and boost the catalysis in OER. In its general term, the combination between Cr-based and Cu-based catalysts exhibited promising activities in various applications [37][38][39][40]. Particularly, they demonstrated near those of precious metal-based catalysts in auto-emission control.…”
Section: Introductionmentioning
confidence: 99%
“…The coarse microstructure of the exposed polyimide indicates the emission of volatile species and severe failure. 33 The AO erosion kinetic and morphological variations of the ZnO/CuNi-polyimide composite film are shown in Figure 4A,B. After composite film deposition, E y decreases by 43.6-fold.…”
Section: Ground-based Ao Exposurementioning
confidence: 99%
“…Our previous work has demonstrated that CrO x /CuNi-polyimide composite films based on multitechnology integration show good AO resistance and electrostatic dissipation as they ensure sufficient interfacial adhesion strength. 33 However, the accumulation of O in CrO x films can lead to toughness reduction, crack initiation, and propagation, resulting in the interface delamination and debonding of the composite films. In addition, apparent holes and local amorphous state of the Fe + -irradiated CrO x can be detected after a high irradiation dose of 10 17 atoms/cm 2 , and its lattice swelling rate is approximately 11.22%.…”
Section: Introductionmentioning
confidence: 99%